2000
DOI: 10.1136/bmj.320.7242.1112
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aggression in psychiatric admissions: semistructured interview and case note survey

Abstract: Most mentally ill people are not violent, and most violence is carried out by mentally well people. 1 Nevertheless psychiatric illness is associated in the public mind with violence.2 3 Psychiatric assessment routinely examines suicidality, but how commonly clinicians ask patients about other forms of aggressive ideation is unclear.We aimed to measure the prevalence of aggressive ideation among patients admitted to psychiatric hospitals, and how frequently examining psychiatrists asked about such thoughts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 4 publications
1
13
0
3
Order By: Relevance
“…Mental health and community-based services therefore need to be aware of the potential risk posed by the carrying of weapons, particularly if there is evidence of paranoid ideation or persecutory beliefs. Clinicians also have a responsibility to routinely to incorporate questions regarding the carrying of weapons and weapon use into standardised risk assessment (Sanders, Milne, Brown, & Bell, 2000) and be aware of any requirements to inform potential victims of the possibility of violence occurring (Ferris et al, 1997). Additionally, medication and cognitive therapy to reduce perceptions of threat may reduce the propensity to carry weapons and thereby the likelihood of violence (Arseneault, Moffitt, Caspi, Taylor, & Silva, 2000;Joyal et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Mental health and community-based services therefore need to be aware of the potential risk posed by the carrying of weapons, particularly if there is evidence of paranoid ideation or persecutory beliefs. Clinicians also have a responsibility to routinely to incorporate questions regarding the carrying of weapons and weapon use into standardised risk assessment (Sanders, Milne, Brown, & Bell, 2000) and be aware of any requirements to inform potential victims of the possibility of violence occurring (Ferris et al, 1997). Additionally, medication and cognitive therapy to reduce perceptions of threat may reduce the propensity to carry weapons and thereby the likelihood of violence (Arseneault, Moffitt, Caspi, Taylor, & Silva, 2000;Joyal et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The evolving mental health services witnessed the demise of traditional mental health hospitals with a policy of more open community services. There continues to be an escalation in violence, and it has been identified, [8] that almost a quarter of patients admitted to hospital reported thoughts of violence directed at specific individuals. The relationship between the use of illegal drugs and violence is increasing, and almost two decades ago, the illicit use of drugs among psychiatric inpatients as a major security issue, was highlighted [9].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical experience suggests that the risk for violence is frequently overlooked by clinicians [2]. A very recent article of Sanders et al [3] showed that patients are frequently asked about suicidal ideas by the treating team but only 13 % had been asked about thoughts of interpersonal violence. 24 of 114 patients interviewed had violent thoughts about specific individuals.…”
Section: Assessment Of Violence and Aggression In Schizophreniamentioning
confidence: 98%